ANALISIS KEBIJAKAN PENYAMPAIANSUSTAINABILITY REPORTING - Linda, Linda (Universitas Pendidikan Indonesia, 2019)
Sustainability reporting in Indonesia is voluntary not mandatory, there for, it is needed firm policy on its implementation. A theoretical model supply and demand for socially responsible investment is still argues, whether these activities will improve, reduce or have no impact on a firm’s market value. This research aim to determine the differences in firm performance between the firm that do sustainability reporting and those don’t sustainability reporting in IDX. The result shows that no significant difference in firm performance between the firm that do sustainability reporting and don’t sustainability reporting. This supply and demand condition is not favorable cause of the implementation of sustainability reporting have no impact on firm performance.